Employability Analysis of Students in Yogyakarta: Confirmatory Factor Analysis - Bambang Sudarsono; Fatwa Tentama; Fanani Arief Ghozali (AL-ISHLAH: Jurnal Pendidikan, 2022)
The employability of students is an essential factor that every school must consider. This study aims to test the validity and reliability of the employability scale construct, determine the contribution of each aspect and indicator in reflecting employability variables, and test whether the theoretical model of employability fits with empirical data. Employability is measured by four aspects, namely skills, knowledge, understanding, and personality attributes. The subjects in this study were 372 students of State Vocational High School 1 Kalasan Yogyakarta. The sample in this study amounted to 225 students. The sampling technique used probability sampling with simple random sampling. The data collection method used a job satisfaction scale and data analysis using Structural Equation Modeling (SEM) with 2nd Order CFA through Lisrel 8. 71 programs. The analysis results show that students at the State Vocational High School 1 Kalasan have employability in the reasonably high category. The aspects and indicators that make up the employability variables are declared valid and reliable based on the analysis results. The most dominant aspect that reflects employability is the scientific aspect, namely studying the material presented in school. The lowest aspect that reflects employability is the personality aspect, namely the perception of online to take risks for what is done. The employability variable measurement model fits the empirical data. The main fit model criteria used in testing the suitability of this model are Chi-Square p, RMSEA, NFI, NNFI, CFI, IFI, GFI, AGFI.